Rapid and efficient microwave-assisted synthesis of Mn-doped cesium bromide to phase engineered cesium manganese bromide nanocrystals with color-tunable RGB emission - Sahu, Pragati; Mukherjee, Shatabdi Porel (Journal of Materials Chemistry C, 2025)
Lead-free perovskite nanocrystals (NCs) have attracted considerable attention due to their excellent optoelectronic properties. However, they generally exhibit broadband emission with poor color purity. Similarly, obtaining tunable red/green/blue (RGB) emissions from lead-free perovskite NCs is highly desirable for several display applications. However, directly synthesizing lead-free perovskite NCs with tunable RGB emission and high color purity remains challenging. Herein, we have developed a simple and rapid microwave-assisted (MW-AT) synthesis strategy for synthesizing Mn-doped CsBr [Mn2+:CsBr] to phase engineering of non-toxic and stable all-inorganic cesium manganese bromide perovskite NCs in a nonpolar solvent with tunable blue-green-red emission color with high color purity. The phase transition was triggered by changing the MnBr2 concentration during the microwave synthesis: from Mn2+:CsBr (blue emission) to zero dimensional (0D) Cs3MnBr5 NCs (green emission) to one dimensional (1D) CsMnBr3 NCs (red emission). In addition, in a controlled moisture environment, both the 0D Cs3MnBr5 and 1D CsMnBr3 NCs were transformed into 0D Cs2MnBr42H2O NCs (blue emission), which could be inversely transformed back to their respective original phase via thermal annealing. Thus, our work highlights for the first time a rapid and efficient MW-AT synthesis strategy to obtain phase-pure tunable optical properties with high color purity from Mn-doped CsBr to cesium manganese bromide perovskite NCs via phase engineering, which can be further utilized in designing anti-counterfeiting and encryption materials for coding with high security and information concealment. Our work also provides a new avenue for exploring efficient MW-AT synthesis of other earth-abundant eco-friendly highly luminescent Pb-free perovskite NCs for future endeavors.